2022
DOI: 10.1111/jar.12996
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drugs intake in people aging with intellectual disability: Prevalence and predictors

Abstract: Background: Psychotropic medication is frequently administered to people with intellectual disability with mental health and/or behavioural problems, instead of other non-pharmacological interventions. This study describes the mental health and behavioural problems of people aging with intellectual disability, their psychotropic medication intake, and the factors contributing to a greater medication intake. Method:The sample consisted of 991 people with intellectual disability over 45 years. Descriptive statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Our study descriptively analyzed patterns of psychotropic medication use in our sample. Consistent with the work of other researchers (Esler et al, 2019 ; García-Domínguez et al, 2022 ; Lunsky & Modi, 2018 ) we found widespread use of medications to manage mental health and behavioral conditions, even when formal diagnoses were not noted. We also found that NCI-IPS respondents were more likely to use medications to manage behavioral support needs than they were to have a behavior management plan on file.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study descriptively analyzed patterns of psychotropic medication use in our sample. Consistent with the work of other researchers (Esler et al, 2019 ; García-Domínguez et al, 2022 ; Lunsky & Modi, 2018 ) we found widespread use of medications to manage mental health and behavioral conditions, even when formal diagnoses were not noted. We also found that NCI-IPS respondents were more likely to use medications to manage behavioral support needs than they were to have a behavior management plan on file.…”
Section: Discussionsupporting
confidence: 92%
“…Part of the challenge in determining rates of mental health conditions and behavioral support needs behavior among people with IDD is disentangling the complex relationships between these constructs. For example, higher levels of intellectual disability (severe or profound) were associated with higher rates of documented behavioral support needs (García-Domínguez et al, 2022 ; Kats et al, 2013 ; Scott & Havercamp, 2014 ) and lower rates of mental health diagnoses (Scott & Havercamp, 2014 ), compared with people with mild or moderate IDD. McCarthy et al ( 2010 ) analyzed clinical assessments from a specialist mental health service and reported that more severe levels of ID positively predicted challenging behaviors while a mental health diagnosis did not.…”
Section: Interactions Between Idd Mental Health and Behavioral Suppor...mentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is recommended that long-term off-label psychotropic drug prescription should be discontinued especially antipsychotics, they are still frequently prescribed for the treatment of challenging behaviours [ 34 , 35 , 36 ]. This may, at least partially be, because of failures of successful discontinuation of antipsychotics due to worsening of behaviour upon drug withdrawal [ 37 ].…”
Section: Introductionmentioning
confidence: 99%